Thermodynamic analysis of a gasifier-based coal-to-fuel cogeneration system. (24th February 2020) - Alharthi, Mathkar A.; Khaliq, Abdul; Luqman, Mohammad
In this paper a thermodynamic model has been developed for the analysis of a coal gasifier based cogeneration system. The influence of the pressure ratio, turbine inlet temperature and pinch point is ascertained on cogeneration performance. Elevation of gasifier pressure leads to decrease the first law efficiency of cogeneration but a small gain in its second law efficiency is observed. Both first and second law efficiencies of cogeneration decrease with increasing the pinch point temperature, however, the increase of pinch point temperature involves a significant rise of power to heat ratio. A considerable improvement in the performance parameters of cogeneration is observed with the rise of turbine inlet temperature. Irreversibility rates of 5, 994 kW and 2, 597 kW are found in the combustion chamber and HRSG, respectively. Increasing the gasifier pressure enhance the first law efficiency of cogeneration but provides a small gain in the second law efficiency of cogeneration.